Improving preparedness for mass casualty incidents in hospitals: Insights from a Large-Scale Simulation Exercise with Geotracking and Validated Questionnaires - Forst, Maik von der; Schäfer, Hanne; Mohr, Stefan; Kenngott, Hannes Götz; Farjallah, Elyes; Huck, Matthias; Baetzner, Anke; Frenkel, Marie Ottilie; Ries, Markus; Loos, Martin; Michalski, Christoph; Leowardi-Bauer, Christine; et al. (Research Square, 2025)
Background: - Mass casualty incidents (MCIs) rapidly exceed routine hospital capacity. Full-scale exercises are essential for preparedness, but systematic, multidimensional evaluations remain scarce. This study aimed to evaluate overall team performance in triage accuracy, workflow, and individual workload throughout a MCI exercise. - Methods: - In a prospective observational study at Heidelberg university hospital (Germany), healthcare professionals managed 91 simulated casualties using a two-stage triage process. Patients and staff carried location tags enabling continuous spatiotemporal tracking. Objective outcomes included triage accuracy, triage duration, patient flow, and staff-patient contact frequency. Subjective workload and teamwork were assessed using the NASA Task Load Index (NASA-TLX) and the Team Emergency Assessment Measure (TEAM), respectively. - Results: - Overall triage accuracy was 75.4%. Undertriage occurred in 11.6% of category I and 10.1% of category II cases; overtriage was infrequent (2.9%). Mean triage times differed significantly by category: ‘red’ 59 ± 25 s, ‘yellow’ 173 ± 74 s, ‘green’ 205 ± 100 s (p < 0.0001). Geotracking demonstrated consistent patient flow without detectable bottlenecks and a mean of 7.1 ± 5.7 patient contacts per staff member. NASA-TLX scores indicated high temporal demand but low frustration with an overall workload of 66.7 ± 16; specialists and staff with greater professional experience reported significantly lower workload (p < 0.05). TEAM ratings were homogeneously high across all participants (79.8%). - Conclusions: - This study provides reproducible benchmark data on hospital MCI response. The integration of geotracking with subjective measures, enables a comprehensive evaluation of hospital disaster preparedness. Moreover, the ability to compare different exercises and collect reliable longitudinal data may further enhance hospital disaster response.